The first‐in‐human study of CNTO 7160, an anti‐interleukin‐33 receptor monoclonal antibody, in healthy subjects and patients with asthma or atopic dermatitis. Issue 12 (14th June 2020) - Nnane, Ivo; Frederick, Bart; Yao, Zhenling; Raible, Donald; Shu, Cathye; Badorrek, Philipp; van den Boer, Maarten; Branigan, Patrick; Duffy, Karen; Baribaud, Frédéric; Fink, Damien; Yang, Tong‐Yuan; et al.
Abstract : Aims: To assess safety, tolerability, pharmacokinetics (PK), pharmacodynamics (PD) and immunogenicity of CNTO 7160, an anti‐interleukin‐33 receptor (IL‐33R) monoclonal antibody, in healthy subjects and patients with asthma or atopic dermatitis (AD). Methods: In Part 1 of this Phase I, randomized, double‐blind, placebo‐controlled study, healthy subjects ( n = 68) received single ascending intravenous (IV) CNTO 7160 dose (0.001 to 10 mg/kg) or placebo. In Part 2, patients with mild asthma ( n = 24) or mild AD ( n = 15) received 3 biweekly IV CNTO 7160 doses (3 or 10 mg/kg) or placebo. Results: CNTO 7160 was generally well tolerated, with 1 serious adverse event of severe cellulitis reported (AD, CNTO 7160, 3 mg/kg). CNTO 7160 exhibited nonlinear PK (0.01–10 mg/kg). Mean clearance decreased with increasing dose (2.43 to 18.03 mL/d/kg). CNTO 7160 PK was similar between healthy subjects and patients with asthma or AD (3 or 10 mg/kg). Free sIL‐33R suppression was rapid and dose dependent. Ex vivo inhibition of p38 phosphorylation of basophils was dose‐dependent (1–10 mg/kg) and sustained inhibition (≥75%) was observed at higher doses (3 or 10 mg/kg). PK/PD modelling and simulation suggests that 1 mg/kg IV every 2 weeks provides adequate systemic drug exposure for sustained inhibition of p38 phosphorylation of basophils. Despite confirmation of target engagement, no apparent CNTO 7160 clinical activity was observed in patients (asthma or AD). Conclusion: This first‐in‐human study provides PK, PD and safety data, supporting further clinical investigation of CNTO 7160 in patients with asthma and AD.